Diseño de una planta de tratamiento de aguas residuales municipales para el distrito de Santiago de Chuco - Paz García, Abraham Eduan (2017)
A plant has been designed for the treatment of municipal wastewater in the District of Santiago de Chuco, using the design methodology according to the National Building Regulations, DS N ° 011-2006-HOUSING, standard OS.090 Water treatment plants Residual; And the Technical Regulation of the Drinking Water and Basic Sanitation Sector, RAS-2000, as a complementary methodology. It began with the compilation of necessary bibliographical information, projection of populations, and methodology of design of treatment units, among others. Subsequently, the flow measurements were taken to determine the sampling protocols that were between 11:00 and 13:00 hours; (BOD5, STD, SS, COD, conductivity, oils and grease, pH, Temperature), the results of which are referential, due to the fact that there is some uncertainty in The means for conducting the analyzes. Following the design methodology mentioned, and based on the reference values obtained in the characterization, the type of treatment, which is by activated sludge, was determined, and the treatment systems that would be included; And then, in Excel books, we proceeded to size each of the physical units: Incoming channel, degenerator and grids as pretreatment; Primary settler as primary treatment; And the active sludge system and drying bed as secondary treatments; The same ones, which were drawn in the AutoCAD program at the basic plane level. The location of the project was also suggested based on the Technical Regulations of the Water Supply and Sanitation Sector. The efficiency of removal of BOD5 from the proposed plant is 94%, a range that complies with what is established by the regulations; in addition, it is suggested complementary studies to determine some alterations in the operation of the process because it is relatively new in the environment